1995
DOI: 10.21000/jasmr95010186
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Grasslands: I. The Importance of Traditional Management Practices

Abstract: Since the l 930's there has been a loss of some 6. 7 million hectares of lowland semi-natural grassland in the UK. As a consequence many of the remaining grasslands of nature conservation importance have been given statutory protection. However, planning pennission can be granted for developments such as mining, and as a result transplantation may be undertaken as a mitigation measure.TI1ere has been concern and debate about transplantation, because of significant changes in botanical composition and loss of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…The botanical composition and conservation value of grasslands in the UK coalfields had been described by Humphries, et. al., (1991) and included the communities and species of importance and particular conservation value in the South Wales Region.…”
Section: Mg5/mg8mentioning
confidence: 92%
“…The botanical composition and conservation value of grasslands in the UK coalfields had been described by Humphries, et. al., (1991) and included the communities and species of importance and particular conservation value in the South Wales Region.…”
Section: Mg5/mg8mentioning
confidence: 92%
“…Intervention during the preparation for the implementation of the translocation of habitats, and subsequently, is likely to be required on several accounts (Humphries et al, 1995;Down and Morton, 1998;Anderson, 2003;Humphries, 2016;Buckley et al, 2017). This includes the likely coppicing/pollarding of trees/shrubs to be transferred, control of invasive competitive species and browsing mammals, and the later management of the structural architecture of the developing woodland.…”
Section: Intervention As Normal Practicementioning
confidence: 99%
“…Where it is necessary to transplant thick turves (ie > I00-150mm), the thickness must be closely monitored and tightly controlled, relayed turves should be carefully pressed, regular gaps between turves must be left and carefully backfilled. Where these measures are fully implemented, traditional grazing and cutting management should be possible (Humphries et al, 1995). It should therefore be possible to maintain the nature conservation value of transplanted pastures and meadows.…”
Section: Unevennessmentioning
confidence: 99%
“…In our first paper on grassland transplantation (Humphries, Horton & Benyon, 1995) we concluded that the ability to graze and/or cut the transplanted grasslands in their traditional manner was crucial to their long term success. However, from the examples we used and others we have recently described (Horton and Benyon, 1993), it is cleat that traditional management has not generally taken place, and as a result many transplants have not been as successful as they might otherwise have been.…”
Section: Introductionmentioning
confidence: 99%